A comparative study on hydrochemical evolution and quality of groundwater in coastal areas of Thailand and Bangladesh. (15th June 2020) - Xiong, Gui-Yao; Chen, Guang-Quan; Xu, Xing-Yong; Liu, Wen-Quan; Fu, Teng-Fei; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Ali Seddique, Aahraf; Shi, Xue-Fa; Liu, Sheng-Fa; Su, Qiao; Xu, Xiu-Li
Graphical abstract: Highlights: Over-exploitation contributes to groundwater pollution in Thailand and Bangladesh. Seawater intrusion causes groundwater pollution in Thailand especially F pollution. Human pollutant causes water pollution in Bangladesh especially Fe, Mn pollution. Na + /HCO– 3 promote F enrichment, Na + (K + /Ca 2+ /Mg 2+ ) promote Fe, Mn enrichment. Different policy recommendations were given for Thailand and Bangladesh. Abstract: In recent years, Thailand and Bangladesh have been drawing more attention due to groundwater pollution, but there is rarely a comparative study on hydrochemical evolution and quality assessment of groundwater in the areas In this paper, end-member mixing and Gibbs model are used to study the evolution of groundwater hydrochemistry based on the 74 water samples. Due to the seawater intrusion, the evolution path of groundwater in Bangkok Bay is Ca/Mg-HCO3 → Na (Ca/Mg)-HCO3 and Na (Ca/Mg)-Cl → Na-Cl, which led to increased Na +, K +, and HCO3 – concentrations in groundwater and enrichment of fluorine in groundwater caused fluorine pollution. In contrast, although the evolution path of groundwater in southern Bangladesh shows a similar pattern as Ca/Mg-HCO3 → Na (Ca/Mg)-HCO3 and Ca/Mg-Cl → Na-Cl, the principal influence factors are residential, agricultural and industrial pollutants. The scope of seawater intrusion is only limited to estuary areas of the southern estuary, whereas most groundwater is received recharge of polluted surface water, which resulted in the enrichment of Fe and Mn. In addition, compared with shallow groundwater, deep groundwater is updated slowly and evolved to higher degree, and is in the Na (Ca/Mg)-HCO3 and Ca/Mg-Cl stage. For improving groundwater conditions in southern Bangladesh, enhancing the supply capacity of surface potable water and significantly reducing groundwater exploitation are priority. Strictly controlling the generation, storage and treatment of domestic waste, industrial and agricultural pollutants are also important. In Bangkok Bay, reducing the groundwater exploitation and dispersing the exploitation area is required.